Lightweight SFRC Benefitting from a Pre-Soaking and Internal Curing Process - Hornakova, Marie; Katzer, Jacek; Kobaka, Janusz; Konecny, Petr (Materials (Basel, Switzerland), 2019)
The presented research program is focused on the design of a structural lightweight fiber-reinforced concrete harnessing an internal curing process. Pre-soaked waste red ceramic fine aggregate and pre-soaked artificial clay expanded coarse aggregate were utilized for the creation of the mix. Copper-coated steel fiber was added to the mix by volume in amounts of 0.0%, 0.5%, 1.0%, and 1.5%. Test specimens in forms of cubes, cylinders, and beams were tested to specify the concrete characteristics. Such properties as consistency, compressive strength, splitting tensile strength, static and dynamic modulus of elasticity, flexural characteristics, and shear strength were of special interest. The achieved concrete can be classified as LC12/13. A strength class, according to fib Model Code, was also assigned to the concretes in question. The proposed method of preparation of concrete mix using only pre-soaked aggregate (with no extra water) proved to be feasible.
Keywords: waste ceramic; SFRC; sustainability; recycling; internal curing